Respuestas
Respuesta dada por:
0
Saludos
(Y^2+2)3
![( y^{2}+2) ^{3} = ( y^{2}) ^{3} +3(y^{2}) ^{2} (2)+3(y) (2)^{2} + 2^{3} ( y^{2}+2) ^{3} = ( y^{2}) ^{3} +3(y^{2}) ^{2} (2)+3(y) (2)^{2} + 2^{3}](https://tex.z-dn.net/?f=%28+y%5E%7B2%7D%2B2%29+%5E%7B3%7D+%3D++%28+y%5E%7B2%7D%29+%5E%7B3%7D+%2B3%28y%5E%7B2%7D%29+%5E%7B2%7D+%282%29%2B3%28y%29+%282%29%5E%7B2%7D+%2B+2%5E%7B3%7D+)
Es la expresión pedida
Espero te sirva
(Y^2+2)3
Es la expresión pedida
Espero te sirva
Respuesta dada por:
0
Aplicas productos notables.
(a + b)³ =
a³ + 3a²b + 3ab² + b³
(a² + 2)³ =
(y²)³ + 3(y²)²(2) + 3(y²)* 2² + 2³ =
y⁶ + 6y⁴ + 3y² * 4 + 8 =
y⁶ + 6y⁴ + 12y² + 8
Respuesta.
y⁶ + 6y⁴ + 12y² + 8
(a + b)³ =
a³ + 3a²b + 3ab² + b³
(a² + 2)³ =
(y²)³ + 3(y²)²(2) + 3(y²)* 2² + 2³ =
y⁶ + 6y⁴ + 3y² * 4 + 8 =
y⁶ + 6y⁴ + 12y² + 8
Respuesta.
y⁶ + 6y⁴ + 12y² + 8
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años